Adobe Photoshop Lightroom 3 on demand - LoCascio, Ted (Que ;, 2010)
Spend less time reading, more time learning. Master Adobe Photoshop Lightroom 3 from start to finish - fast! Up-to-the-minute quick-reference material and hands-on training in an easy-to-use color format Includes extensive bonus online workshop content Covers all day-to-day techniques needed to import, organize, tag, edit, enhance, and output images Reflects major Lightroom improvements in file import, watermarking, slideshows, print packaging, and more Adobe Photoshop Lightroom 3 On Demand is built from the ground up for today's photographer or graphic designer. Like every book in the On Demand Series, this book teaches visually, using an easy, friendly, full-color format designed to "show how," instead of "telling how." But that's not all. This book: " Combines step-by-step training with quick-reference material users can rely on long after they've mastered the core skills they need " Provides easy-to-follow task-based coverage, in which most tasks are presented on convenient 2-page spreads " Provides additional end-of-chapter Step-by-Step Training workshops for readers who like to learn through hands-on projects - with all project assets online at www.queondemand.com " Helps upgraders by presenting a detailed list of new features, indexed to the pages where these features are covered Adobe Photoshop Lightroom 3 On Demand offers tightly focused coverage of the techniques Lightroom users will use most often, including: importing, organizing, and tagging photos; applying edits and enhancements; managing photo libraries; outputting images to printers or online galleries; and more. It covers major improvements to Lightroom 3 file importation, watermarking, slideshow creation, print packaging, and much more. Simply put, for beginning-to-intermediate-level Lightroom users, no other book offers this much simplicity, usable content, flexibility, and value.
Keywords: Adobe Photoshop lightroom; Photography -- Digital techniques -- Computer programs; Photographie numérique; Logiciels